A novel adaptive algorithm for 3D finite element analysis to model extracortical bone growth. Issue 2 (25th January 2018) - Cheong, Vee San; Blunn, Gordon W.; Coathup, Melanie J.; Fromme, Paul
Abstract: Extracortical bone growth with osseointegration of bone onto the shaft of massive bone tumour implants is an important clinical outcome for long-term implant survival. A new computational algorithm combining geometrical shape changes and bone adaptation in 3D Finite Element simulations has been developed, using a soft tissue envelope mesh, a novel concept of osteoconnectivity, and bone remodelling theory. The effects of varying the initial tissue density, spatial influence function and time step were investigated. The methodology demonstrated good correspondence to radiological results for a segmental prosthesis.